Genome Analysis of Thinopyrum intermedium and Its Potential Progenitor Species Using Oligo-FISH - Fei Qi; Shuang Liang; Piyi Xing; Yinguang Bao; Richard R.-C. Wang; Xingfeng Li (Plants, 2023)
The genome composition of intermediate wheatgrass (IWG) is complex and continues to be a subject of investigation. In this study, molecular cytogenetics were used to investigate the karyotype composition of Th. intermedium and its relative diploid species. St2-80 developed from Pseudowroegneria strigose and pDb12H developed from Dasypyrum breviaristatum were used as probes in fluorescence in situ hybridization (FISH) to classify the chromosomes of Th. intermedium into three groups, expressed as JvsJvsJrJrStSt. A combined multiplex oligonucleotide probe, including pSc119.2-1, (GAA)10, AFA-3, AFA-4, pAs1-1, Pas1-3, pAs1-4, and pAs1-6, was used to establish the FISH karyotype of ten accessions of Th. intermedium. Variability among and within the studied accessions of intermediate wheatgrass was observed in their FISH patterns. Results of this study led to the conclusions that Jvs had largely been contributed from Da. breviaristatum, but not the present-day Da. villosum; IWG had only one J genome, Jr, which was related to either Th. elongatum or Th. bessarabicum; and St was contributed from the genus Pseudoroegneria by hybridization with Th. junceiforme or Th. sartorii.